A study on the establishment of a municipal library in Naguilian, Isabela - Lamorena, Sonntag Santy S. (2005)
As mandated by Republic Act 7743 "An Act Providing for the Establishment of Congressional, City and Municipal Libraries and Barangay Reading Centers Throughout the Philippines, Appropriating the Necessary Funds Therefore and For Other Purposes.", the local government of Naguilian is required to put up a a public library in their area. The Municipal Government of Naguilian has already made initial steps towards recognizing the mandate of RA 7743 through the passing of SB Resolution no 2001-009 in March of 2001, however to this day no municipal library exists in Naguilian.